RANCANG BANGUN SISTEM OTOMASI PADA RUMAH KACA TANAMAN HIDROPONIK BERBASIS MIKROKONTROLLER ESP 8266 - Sadi, Sumardi; Saputra, Wardhani Eka (Jurnal Teknik Elektro, 2024)
Currently, the activity of gardening has developed rapidly from the past to the present. However, we do not have much land in urban areas due to the increasing population. Consequently, the yield of vegetable crops has decreased, and thus, we need to adapt to the changing times. At present, we have modern gardening techniques using water and limited land, such as Hydroponic cultivation. The purpose of this research is to design and build an automated system to care for Hydroponic plants, including maintaining pH and nutrient levels according to the required standards. The method used is qualitative, where the testing of the device is conducted. The design and construction of an automatic irrigation control system and IoT-based monitoring using NodeMCU 8266, pH sensor, TDS sensor, temperature sensor, and humidity sensor are implemented. This tool was created as a solution to maintain a stable pH of around 5-5 to 7, maintain nutrients around 650-850, maintain a temperature of around 28 degrees and below, and can be monitored by the owner via an internet network which can be accessed via smartphone as the name suggests, namely Internet-based. of Things (IoT). The result of maintaining this stability is good and quality plants.